Improving Creative Thinking Skills with the STEM Learning Model for Fifth Grade Elementary School Students - Rika Putri Yanti; Jajang Bayu Kelana (Jurnal Profesi Pendidikan, 2025)
The purpose of this study was to determine the improvement of creative thinking skills using the STEM (Science, Technology, Engineering and Mathematics) model. This study used a pre-experimental design. The research method used was a quantitative design with One group pretest-posttest. The sample population in this study was 29 students from grade V in elementary school. The results of the pretest and posttest were analyzed using SPSS. To determine the improvement of creative thinking skills, descriptive analysis, normality test, hypothesis test, N-gain test were carried out. From the test, the descriptive statistical results showed that there was an average increase with a difference of 37.07, the results of the normality test of the pretest value were 0.232> 0.05 while the posttest value was 0.93> 0.05. Furthermore, the results of the hypothesis test obtained sig. (2-tailed) of 0.000 <0.05 so Ha was accepted. Then the results of the N-gain value were 0.58 with a fairly effective category. From these results, it can be concluded that the application of the STEM (Science, Technology, Engineering and Mathematics) model can improve the creative thinking skills of fifth grade elementary school students, which has a positive impact on learning.